Faktor-Faktor Yang Mempengaruhi Opini Audit Going Concern Pada Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia (2016–2018) - Sriyunia Anizar; Fahmi Rizani; Ade Adriani (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
In 2016, the online media, kontan.com, stated that not all issuers listed on the IDX have a business continuity. In 2018 cases of misuse of funds had a significant impact on the company's going concern (SNP) involving KAP. The purpose of this research is to examine the effect of company growth, ROA, audit tenure, KAP reputation on giving going concern audit opinion, opinion shopping on giving going concern audit opinion, previous year's audit on going concern audit opinion.This research is an associative quantitative study with the unit of analysis of audited financial statements and independent auditor reports issued by KAP. This study uses secondary data, data analysis techniques used logistic regression with SPPS version 26 software. The sample selection using purposive sampling method. The research results show that the influence of company growth, audit tenure, KAP reputation and opinion shopping has no effect on going concern audit opinion, while ROA and previous year's audit opinion has an effect on going concern audit opinion.